Public speaking for personal success - Hanna, Michael S.; Gibson, James W. (Needhman: Pearson custom publishing, 1999)
Contents: part 1. speaking and listening. part 2. designing the speech. part 3. organizing the speech. part 4. delivering the speech. part 5. common types of speeches.
Keywords: Hablar en Público